Comparative Study of HTB and PCQ Methods for Bandwidth Limitation in SDS IT Sahabat Muslim - Safrianti, Ery; Linna Oktaviana Sari; Wijaya, Alvansya Hawari (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2025)
A stable Internet connection is needed to make it easier to manage school data. However, the more teachers or students who use the Internet simultaneously without any bandwidth management, the more it will affect the speed of the Internet connection and decrease its performance. Based on these problems, bandwidth limitation is needed to limit speed and maintain bandwidth quality so that the Internet remains optimal even though it is being used simultaneously. Several bandwidth limitation methods can be applied, including the Hierarchical Token Bucket (HTB) and Peer Connection Queue (PCQ) methods. Tests are needed to determine which method is more suitable to implement. In this study, the two methods will be applied to SDS IT Sahabat Muslim to analyze these two methods. Each bandwidth management method was applied, and several tests were carried out, such as internet speed testing, watching online videos via YouTube, testing virtual meetings using Zoom, and testing downloading files. Then, a comparison was made from the results of the trials of each method, and the results showed that the PCQ method was more suitable to be applied at SDS IT Sahabat Muslim than the HTB with average throughput for speed test, YouTube, zoom, download, and upload respectively 1107 kbps, 1154 kbps, 1226 kbps, 1452 kbps, and 1441 kbps and delay of around 6.74 ms.